The Effect of Personal Engineering Ability and Information Technology Sophistication on the Effectiveness of Accounting Information Systems - Ade Wiandika Anatasya Putri; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2026)
This study aims to examine and provide empirical evidence regarding the effect of personal technical skills and information technology sophistication on the effectiveness of Accounting Information Systems (AIS). SIDI Sanur with 14 Savings and Loan Units (USP) as research samples. This research uses non-probability sampling method with purposive sampling technique, and produces 51 research respondents. Data collection was carried out using a survey method with a questionnaire technique. The analysis technique in this study uses multiple linear regression analysis. The results of the analysis show that both personal technical skills and information technology sophistication have a positive effect on the effectiveness of accounting information systems. The results of this study can be taken into consideration for companies to be able to measure the extent to which their employees are able to use sophisticated systems.